"ANALYSING THE TRENDS AND CHALLENGES IN THE PRODUCTION AND PROCESSING OF FOOD" - Naeem Pathan; Swapnil Salvi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Conserving foods includes several processing processes in order to keep food quality at the required level in order to obtain maximum benefits and nutritional qualities. Methods of food conservation include food production, caught, processed, packaged and distributed. This opinion article addressed historical, contemporary and future food processing problems. If only fresh methods can conquer new difficulties, new food processing possibilities are created. Themes such as safety, preserving, nutrition, sensory, well-being, environment and potential for future problems were addressed.